Climate Change and its Environmental Implications for Sustainable Energy in Iraq Using GIS and RS (Iraqi National Journal of Earth Science (INJES), 2026)
This research investigates climatic changes, their core indicators, and their environmental repercussions on renewable energy sources in Iraq. The study analyzes meteorological data from fourteen (14) stations comprehensively covering Iraq's geographical diversity from north to south and east to west. Advanced spatial and statistical software, including ArcGIS (V.10), ERDAS Imagine, ILWIS (V.3.7), and SPSS (V.16), were utilized alongside mathematical formulations, linear regression, and correlation analyses to process spatial visuals and carbon dioxide (CO2) emission trends. The findings indicate a significant shift in climatic elements: a continuous rise in average temperatures, elevated evaporation rates, and increased solar radiation intensity, contrasted by a decrease in average wind speeds and annual rainfall. Additionally, an increase in the frequency and severity of dust storms and greenhouse gas emissions was observed. A Geographic Information Systems (GIS) database was constructed to map regions demonstrating high efficiency for renewable energy production. Spatial analysis revealed that the Nasiriyah, Al-Amarah, Najaf, and Samawah stations are highly efficient for solar energy harvesting. Conversely, wind energy potential peaked at the Basra, Najaf, Samawah, and Wasit stations, while hydroelectric power generation experienced noticeable recessions at major dam reservoirs, including Mosul, Dukan, and Darbandikhan dams, due to water scarcity.
Keywords: Climate change - global warming - indicators of the electricity sector hydropower - solar radiation climate requirements - sustainable energy